2003
DOI: 10.1189/jlb.0703303
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 receptor activation reduces mouse myocardial ischemia-reperfusion injury: involvement of cytokine/chemokines and PMN

Abstract: In this study, we have assessed the activation of the cannabinoid CB2 receptor (CB2-R) in a model of mouse myocardial ischemia/reperfusion (I/R). The results show that treatment of animals with WIN55212-2, a CB1/CB2-R agonist, given 30 min before induction of I/R, significantly reduced the extent of infarct size (IS) in the area at risk, as measured 2.5 h later, with almost a 51% inhibition observed at the dose tested of 3.5 mg/kg intraperitoneally (i.p.). The protective effect of WIN55212-2 was almost abolish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 41 publications
(44 reference statements)
10
87
0
1
Order By: Relevance
“…Also, ␤ -caryophyllene induces a switch from a TH1 to a TH2 immune response by inhibiting the pathway triggered by activation of the toll-like receptor complex CD14/TLR4/MD2 ( 44 ). Many studies have focused on the role of the CB2 receptor in the anti-infl ammatory and anti-oxidative effects of WIN55,212-2 ( 6,7,(32)(33)(34). In the present study, we observed that the selective CB2 receptor antagonist AM630 blocked the effects of WIN55,212-2 on oxLDL-induced TNF-␣ expression, ROS generation, and ERK1/2 phosphorylation.…”
Section: Win55212-2 Decreases Oxldl-induced Ros Generation In Macropsupporting
confidence: 64%
“…Also, ␤ -caryophyllene induces a switch from a TH1 to a TH2 immune response by inhibiting the pathway triggered by activation of the toll-like receptor complex CD14/TLR4/MD2 ( 44 ). Many studies have focused on the role of the CB2 receptor in the anti-infl ammatory and anti-oxidative effects of WIN55,212-2 ( 6,7,(32)(33)(34). In the present study, we observed that the selective CB2 receptor antagonist AM630 blocked the effects of WIN55,212-2 on oxLDL-induced TNF-␣ expression, ROS generation, and ERK1/2 phosphorylation.…”
Section: Win55212-2 Decreases Oxldl-induced Ros Generation In Macropsupporting
confidence: 64%
“…However, these studies used buffer-perfused, isolated heart preparations and could not address the question of whether endocannabinoids or synthetic agonists can modulate endothelial or immune cell activation and interactions, which are pivotal events in the sequel of reperfusion damage [14,39]. In a more relevant study by using nonselective CB agonist WIN55212-2 and CB 2 antagonist AM630 in a mouse model of myocardial I/R, the reduction of leukocyte-dependent myocardial damage could be attributed to CB 2 receptor activation, as the protection afforded by WIN55212-2 could be prevented by AM630 but not by CB 1 antagonist AM251 [46]. In agreement with those findings, we have recently reported that CB 2 agonist JWH133 afforded protection against hepatic I/R damage by decreasing inflammatory cell infiltration and consequent tissue injury, and CB 2 receptor knockout mice developed increased injury and proinflammatory phenotype following I/R [44].…”
Section: Discussionmentioning
confidence: 99%
“…In an ischemia/reperfusion injury model in rats, both anandamide and HU-210 decreased the incidence of ventricular arrhythmias and reduced the size of the infarct, presumably trough the activation of CB2 receptors but not CB1 receptors (Krylatov et al, 2001). In an myocardic I/R injury model induced by ligation of coronary artery in rats, the reduction of the second myocardic injury depending on leucocytes subsequent to the initial I/R injury was attributed to the activation of CB2 receptors, since the protection given by WIN 55.212-2 could be prevented by AM630, but not by AM251 (a CB1 antagonist) (Di Filippo et al, 2004). Two recent studies in myocardial infarct models, acute and chronic, in rats, showed that cannabinoids contribute to hypotension and cardiac depression associated to cardiogenic acute shock, which could be attenuated by antagonists of CB1 receptors (Wagner et al, 2003).…”
Section: Effects On Myocardial Ischemia/reperfusion and Preconditioningmentioning
confidence: 99%